Closed-loop tool face control with the bit off-bottom. (June 2020) - Auriol, Jean; Shor, Roman J.; Aarsnes, Ulf Jakob F.; Meglio, Florent Di
Highlights: We present a distributed model of a drill string dynamics, where the friction is implemented using an inclusion. We design a soft sensor that estimates the distributed states, the friction coefficients and the tool face orientation. We propose three methods to achieve reliable, closed-loop, tool face control for directional drilling operations. These procedures vary in terms of requirements on available instrumentation, model accuracy and time needed to be completed. These methods are illustrated in simulations on field scenarios. Abstract: In this paper, we develop three methods to achieve reliable closed-loop, tool face control for directional drilling operations. This is a necessary step to achieve closed-loop, automated directional guidance. Our algorithms combine existing industry top-drive controllers with new control approaches. The torsional model we use for the drill string has been field validated and takes into account the Coulomb friction between the drill string and the borehole. These distributed friction terms are either assumed known (or measured) or can be estimated using a state-observer. In this work, we improve such a state-observer to obtain an estimation of the tool face orientation in real-time. We then propose different approaches to control the tool face. The first method is based on a feed-forward control law. It uses the flatness of the model and the estimation of the orientation to generate an admissible trajectory which is then tracked. In the second procedure, we require a stable rotation off-bottom before smoothly changing the reference to zero to stop bit rotation. This change of reference induces a change of orientation that can be estimated and finally compensated by repeating the procedure. Finally, the last method uses a series of trapezoidal setpoint inputs – bumps – to calculate the change in downhole tool face per change in surface orientation before arriving at the correct tool face after three iterations. These three algorithms are illustrated in simulations of field scenarios and their effectiveness and limitations, depending on the reliability and availability of downhole orientation data, are discussed.